Reconceptualising the role of academic language and learning advisers in the artificial intelligence age - Kelly, Andrew; Strampel, Katrina; Lynch, Andrea (Journal of University Teaching and Learning Practice, 2025)
Generative artificial intelligence (AI) tools are profoundly transforming learning, teaching and assessment in higher education. These tools present a major challenge for academic language and learning (ALL) advisers, as they are increasingly capable of performing many of the individual learning support functions that ALL advisers have traditionally provided to students. This conceptual article reimagines the role of ALL advisers in an AI-dominated world. It argues refocusing on four areas of practice: professional learning for educators, AI literacy, peer learning communities, and self-regulated learning. By embracing these areas of practice, and through collaboration with other third space professionals, ALL advisers can leverage the opportunities presented by AI to adopt a leading role in building staff and student